# Butterfly with Menelaus

### Sidney Kung

September 7, 2012

We give a proof of the following by using Menelaus' theorem:

Through a point \(P\) of the line segment \(AB\) whose end points \(A\) and \(B\) lie on two intersecting lines \(l\) and \(l'\), respectively, draw \(CD\) and \(EF\) \((C, F\in l\), and \(E,D\in l')\). Let \(CE\cap AB=X\), \(FD\cap AB=Y.\space\)Then \(PA = PB\) implies \(PX = PY.\)

### Proof

For a repeated application of Menelaus' here, we shall proceed by focusing on parts of the diagram:

- \(\triangle OFE\) cut by transversal \(CPD\)
\(\frac{OC}{CF}\times \frac{FP}{PE}\times \frac{ED}{DO} = 1\).

- \(\triangle OAB\) cut by transversal \(CPD\)
\(\frac{OD}{DB}\times \frac{BP}{PA}\times \frac{AC}{CO} = 1\).

- \(\triangle PBE\) cut by transversal \(FYD\)
\(\frac{PY}{YB}\times \frac{BD}{DE}\times \frac{EF}{FP} = 1\).

- \(\triangle FAP\) cut by transversal \(CXE\)
\(\frac{PE}{EF}\times \frac{FC}{CA}\times \frac{AX}{XP} = 1\).

Multiplying the four identities and simplifying gives \(\frac{PY}{YB}\times \frac{AX}{XP}\times \frac{BP}{PA} = 1\). Since \(PB=PA\), the latter expression further simplifies to \(\frac{AX}{XP}=\frac{YB}{PY}\). Add now \(1\) to both sides: \(\frac{AX+XP}{XP}=\frac{PY+YB}{PY}\), or \(\frac{PA}{XP}=\frac{PB}{PY},\space\)implying \(PX=PY\).

The above proof moved Hubert Shutrick to make the following observation:

The conics of the pencil through \(C\), \(D\), \(E\), \(F\) intersect the line \(AB\) in pairs of points in **involution**. Consider the **degenerate members** \(CD.EF\), \(CE.DF\), and \(l.l'\). \(P\) is a **double point** because of the first and so, if one of the pairs \(A,B\) and \(X,Y\) is symmetrical about \(P\), then so is the other.

|Contact| |Front page| |Contents| |Geometry|

Copyright © 1996-2018 Alexander Bogomolny